La democracia y el progreso ficcional. Análisis e interpretación de los conceptos democracia y progreso en los discursos cinematográficos y teatrales peruanos sobre el conflicto armado interno (1980-2016) - Llanos Argumanis, Ernesto Walter (2021)
This research presents a critical and interpretative analysis about two peruvian films: La boca del lobo (1988) by Francisco Lombardi and La última noticia (2016) directed by Chaski group; and two peruvian theatrical speeches: Sin Título técnica mixta (2004) of the theater group Yuyachkani and the second play is Ruido (2006) directed by Mariana de Althaus, both plays presented in 2016. All of them were made in to referred to the internal conflict lived in Perú between 1980 and 2000.